Sex change in multiple gender sufferers is associated with Islamic law and the Population Administration Law - Utami, Azalia Rahma; Djanuardi, Djanuardi; Rachmainy, Linda (International Journal Labs, 2023)
The phenomenon of transsexuality and sex change is still something that is considered taboo or should not be done by Indonesian society, the reason is because our country upholds religious values, traditions and eastern values adopted by society. Keep in mind that not everyone is born with normal conditions. There are some people who experience gender ambiguity or in medical terms called ambiguous genetalia or sex ambiguity and Islamic jurisprudence studies, this group of people is referred to as khunsa or double gender. The results of this study show that Law Number 23 of 2006 concerning Population Administration opens up opportunities for sex change by submitting a sex change application to the court so that the event can be recorded at the relevant agency. Judging from Islamic law, Islamic law also allows sex change if done for someone suffering from multiple gender conditions (khuntsa) as a form of treatment as stipulated in Fatwa No. 03/MUNASVIII/MUI/2010.